Percutaneous endoscopic intragastric surgery for gastric metastases of renal cell carcinoma: A case report - Hayashi, Saki; Tsuji, Toshikatsu; Tanaka, Hiroyuki; Takenaka, Shunsuke; Machi, Ryosuke; Mitta, Kazuyoshi; Doden, Kenta; Suzuki, Hayato; Shimada, Mari; Saito, Hiroto; Yamamoto, Daisuke; Moriyama, Hideki; et al. (Asian journal of endoscopic surgery, 2024)
To our knowledge, this is the first report of percutaneous endoscopic intragastric surgery (PEIGS) for gastric metastases from other organs. A 70‐year‐old male with a history of renal cell carcinoma (RCC) was referred to our department for the treatment of gastric metastasis of RCC. Partial gastrectomy was performed using single‐incision PEIGS. Two years after the surgery, a follow‐up esophagogastroduodenoscopy revealed a tumor located on the middle greater curvature of the stomach. The diagnosis was metastatic renal cell carcinoma, prompting a similar surgery. No recurrence was observed after the second surgery. PEIGS is a minimally invasive option for the treatment of metastatic gastric tumors.